The Implementation of Children's Song Creation as Character Education through Art for Elementary School Teacher Education Students - Jubelando O. Tambunan; Melisa Nur Asima Sidabutar; Deswidya Sukrisna Hutauruk (CV. Creative Tugu Pena, 2024)
This research aims to develop the skills of PGSD students as prospective teachers in designing teaching materials, namely children's songs as learning media in developing the character of elementary school students. This research is project-based learning (PBL) with a development model Research and Development (R&D) by Borg and Gall. This project-based learning process was carried out by 25 students as research subjects under the guidance and direction of a lecturer who was a researcher himself and carried out in several stages, namely (1) problem identification, (2) information collection, (3) product design, (4) design validation, (5) design improvements, (6) product trials, (7) operational product revisions, (8) usage trials, (9) final stage product revisions, and (10) mass production. The results of this research were that the students were able to create children's songs well, where out of a total of 25 students, they succeeded in creating 25 children's songs with different titles (100%). The children's songs were also assessed based on aspects of suitability to the song theme, song lyrics, tune and suitability to the theme of character education. The results showed that the students were able to create children's songs that contained character education very well (94.4%). So it can be concluded that the PBL process implemented in this research is considered effective in developing teaching materials, especially the aim of this research, namely creating children's songs that contain character education.